Reframing teacher leadership to improve your school - Reeves, Douglas B., 1953- (Alexandria, VA : Association for Supervision and Curriculum Development, 2008)
Offers school leaders practical advice on how they can implement positive changes in their schools and communities through teacher leadership, focusing on the latest research findings, practical applications, and ways to improve student achievement and educational equity.
Why a new framework for teacher leadership? -- The leadership imperative -- The new framework in action -- From reflection to resilience : creating the network for a learning organization -- Barriers to teacher leadership -- How systems support the new framework for teacher leadership.
Includes bibliographical references and index.
Teacher Librarian.
Professional
Keywords: Educational leadership -- United States; School improvement programs -- United States; Teachers -- Training of -- United States; Leadership; Schools -- Administration -- United States; Teachers -- Training -- United States